Subclass of Multivalent Harmonic Functions with Missing Coefficients - R. M. El-Ashwah (International Journal of Mathematics and Mathematical Sciences)
We have studied subclass of multivalent harmonic functions with missing coefficients in the open unit disc and obtained the basic properties such as coefficient characterization and distortion theorem, extreme points, and convolution.